PENERAPAN MODEL PEMBELAJARAN DISCOVERYâ€TRIPLE B-NETâ€ PADA PELAJARAN KARAKTERISTIK NEGARA MAJU DAN NEGARA BERKEMBANG DUNIA SEBAGAI UPAYA MENINGKATKAN KREATIVITAS BELAJAR SISWA - Purwaningsih, Endang (Metafora: Education, Social Sciences and Humanities Journal, 2016)
The results of this study showed that an increase in achievement of learning outcomes from 75% to 90% or an increase of 15%., So researchers hope that learning methods Discovry "TRIPLE B-NET" can be used as a contribution to the learning subjects Integrated IPS particular and other subjects generally PenelitianTindakan this class is implemented with the aim of covering (1) Increase student participation in the learning process. (2). efforts to improve the quality of the methods developed in learning. (3) .Memberi motivation to students to improve their creativity. (4) .Menciptakan the classroom atmosphere more conducive to learning. The benefits of this research is an attempt to help students understand the concept of geography by way of self-learning and creative thinking in order to achieve an increase in creativity to the fullest.